«Invasion Set of Languages»: War of 1812 by Eyes of Soldier’s Foreigners of Great Army - N. A. Kopylov (Vestnik MGIMO-Universiteta)
Article opens features of participation in war of 1812 European soldiers which were a part of army of emperor Napoleon. On the basis of documents of a personal origin the perception of events of campaign of 1812 officers and the soldiers of a foreign origin who were a part of Great army reveals.